A Novel Direct Drive Linear Ocean Energy Converter Based on Nonlinear Oscillator System - Ahamed, Raju (Curtin University, 2022)
This PhD research presents novel analytical, numerical and experimental modelling of single-degree-of-freedom, two-degree-of-freedom and three-degree-of-freedom magnetic spring-based non-linear oscillator systems to harness energy from ocean waves. The proposed energy harvesters overcome the bandwidth problem in the previous linear generator studies which cannot work satisfactorily in the low-frequency range. The outcomes of this research work provide the mathematical foundation for the modelling and upcoming advancement of multi-degree-of-freedom magnetic spring (nonlinear oscillator) based energy generators.